2002
DOI: 10.1262/jrd.48.335
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Equine (Thoroughbred) Myostatin cDNA and Detection of Myostatin Precursor Proteins in the Serum.

Abstract: Abstract. Growth/Differentiation Factor 8, or GDF-8, is a member of the TGF-β family and is expressed specifically in myogenic precursor cells of the myotome during development as well as in adult axial and paraxial muscles of the mouse. It acts as a negative regulator of skeletal muscle mass, and is known as myostatin. As a part of our studies to elucidate mechanisms underlying the growth of skeletal muscle mass due to physical training in mammals including horses and humans, we isolated and cloned myostatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…There are few studies in the horse and to date, only one report has identified myostatin precursor and mature myostatin protein expression in the skeletal muscles ( Semitendinosus, Semimembranosus, Splenius, Gluteus medius) of Thoroughbred and Kiso-uma breeds of horses [19]. That gene and protein expression for myostatin and its receptor were largely exclusive to skeletal muscle, suggested that as reported for other species, myostatin may have an important role in equine muscle function.…”
Section: Discussionmentioning
confidence: 95%
“…There are few studies in the horse and to date, only one report has identified myostatin precursor and mature myostatin protein expression in the skeletal muscles ( Semitendinosus, Semimembranosus, Splenius, Gluteus medius) of Thoroughbred and Kiso-uma breeds of horses [19]. That gene and protein expression for myostatin and its receptor were largely exclusive to skeletal muscle, suggested that as reported for other species, myostatin may have an important role in equine muscle function.…”
Section: Discussionmentioning
confidence: 95%
“…Hosoyama et al . () isolated and sequenced MSTN cDNA from a Thoroughbred horse that was mapped to chromosome 18. Mutations in the equine MSTN have been identified and are associated with racing phenotypes influencing racing performance and muscle fibre proportions (Petersen et al .…”
Section: Myostatin Polymorphisms In Horsementioning
confidence: 99%
“…skeletal muscle [1], it has been reported that myostatin is secreted into the circulation [13][14][15][16]. Some investigators have shown that circulating levels of myostatin-like protein are increased in HIV-infected men and elderly persons with weight loss and muscle wasting symptoms [13,17].…”
mentioning
confidence: 99%